IMPLEMENTATION OF OTTAWA ANKLE RULES IN UNIVERSITY HOSPITAL EMERGENCY ROOM: PILOT STUDY - SACHA PUGLIESE SCHIPER; HUGO MAIA RODRIGUES; JOÃO EDUARDO LIMA ERNESTO REIS; MAYARA BRANCO E SILVA; MAURO DINATO; RODRIGO GONÇALVES PAGNANO (Acta Ortopédica Brasileira, 2023)
ABSTRACT Ankle injuries are the most common musculoskeletal injuries in emergency rooms and are associated with a great social and economic impact. The need to request additional tests for ankle sprains is based on suspicion of fracture. The Ottawa Ankle Rules (OAR) establish criteria for ordering radiographs to avoid performing unnecessary examinations. Objective: To evaluate the implementation of the Ottawa Rules as a protocol for treating ankle sprains in the emergency department of a university hospital. Methods: This is a retrospective observational study, conducted over a period of three months before and three months after implementation of the protocol. Results: In the first phase, all patients complaining of ankle sprain underwent radiographs. In the second phase, after the application of the OAR, out of 85 patients evaluated, only 58 underwent complementary exams, showing a reduction of 31.8% in the request for imaging exams. There was no significant difference in fracture detection between the two groups (p=0.476). Conclusion: The OAR can be used as a tool in diagnosing ankle sprains, and their implementation reduced the request for imaging exams. Level of Evidence III, Retrospective Comparative Study.